2020
DOI: 10.1038/s41467-020-19464-8
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retroviruses form a reservoir of T cell targets in hematological cancers

Abstract: Human endogenous retroviruses (HERV) form a substantial part of the human genome, but mostly remain transcriptionally silent under strict epigenetic regulation, yet can potentially be reactivated by malignant transformation or epigenetic therapies. Here, we evaluate the potential for T cell recognition of HERV elements in myeloid malignancies by mapping transcribed HERV genes and generating a library of 1169 potential antigenic HERV-derived peptides predicted for presentation by 4 HLA class I molecules. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 76 publications
(115 reference statements)
6
50
0
Order By: Relevance
“…Remarkably, the presence of aberrant translation products has recently been demonstrated in various tumor types, including human breast tumors [ 23 ]. Importantly, these candidate tumor antigens can generate specific T-cell responses towards the tumor with clinical relevance [ 11 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the presence of aberrant translation products has recently been demonstrated in various tumor types, including human breast tumors [ 23 ]. Importantly, these candidate tumor antigens can generate specific T-cell responses towards the tumor with clinical relevance [ 11 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These tumor-associated antigens are derived from either tissue-specific or overexpressed proteins in tumor, or proteins expressed in tumor due to epigenetic changes (e.g., cancer testis antigens). Furthermore, endogenous retroviruses (ERVs) are emerging as an interesting source of tumor antigens as their expression in tumor positively associates with immune cell infiltration and even with immune therapy response [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory mechanisms of HERVs are complex and partly vary by HERV groups. Nowadays, studies regarding HERVs are hampered due to a plethora of transcribed HERV RNAs in cancer and the lack of specific commercial antibodies ( 137 ). The emerging high-throughput RNA-sequencing technique may demonstrate a more explicit expression profile of HERVs and expand possible roles in cancer ( 137 , 138 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, studies regarding HERVs are hampered due to a plethora of transcribed HERV RNAs in cancer and the lack of specific commercial antibodies ( 137 ). The emerging high-throughput RNA-sequencing technique may demonstrate a more explicit expression profile of HERVs and expand possible roles in cancer ( 137 , 138 ). Insufficient knowledge regarding HERV genes, their highly complex pattern of activation, and transcriptional and posttranscriptional regulation hinders the ability to study the mechanistic role of HERVs in numerous cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study by Saini et al [ 49 ] evaluated the presence of CD8 + T cell populations reactive to HERV-predicted peptides in PBMCs or BMMCs (bone marrow mononuclear cells) from 34 patients with hematological malignancies, including myelodysplastic syndrome (MDS), chronic myelomonocytic leukemia (CMML) and acute myeloid leukemia (AML), before and after 5-aza-CR treatment. The authors observed a significant enrichment of HERV-reactive T cells in 17 out of 34 patients.…”
Section: Herv Antigensmentioning
confidence: 99%